Management of special physical training of high jumpers based on informative indicators of their condition - Bykov, V. S.; Cherepov, E. A.; Yanchik, E. M.; Tselischev, V. Y. (Theory and Practice of Physical Culture, 2017)
Athletic training management system optimization involves the development and organization of an integrated control system by means of assessing sport results based on model characteristics reflecting athletes` skill level. The article presents various aspects of high jumpers` physical fitness. The analysis of the amplitude (strength and speed) characteristics of movements, obtained during the take-off phase after depth jump revealed the nature of their changes in athletes with different levels of physical fitness.